2018
DOI: 10.3389/fpsyg.2018.02244
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Relationship Between Onset Age of Musical Lessons and Levels of Sociability in Childhood

Abstract: Previous studies have suggested that musical training in childhood is beneficial for sociability. However, it remains unclear how age of onset of group music lessons is associated with the late sociability of children from a long-term perspective. This study investigated associations between group music lessons conducted at a music school and children’s levels of sociability by focusing on the age of onset of the lessons. We conducted a survey of 276 children aged 4–5 years (M = 58.5 months) and 6–7 years (M =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
3
13
0
1
Order By: Relevance
“…There has been a steady decrease in arts and cultural participation between 2008 and 2018 among children in the UK [49,50]. Subjects like Art and Design and Music are not currently included in the national curriculum at secondary Key Stage 4 level (ages around [14][15][16] [51]. Students in schools where these subjects are not available at this level may have limited opportunities to participate in artistic activities during school lessons where supplies, materials and resources are usually provided or subsidised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a steady decrease in arts and cultural participation between 2008 and 2018 among children in the UK [49,50]. Subjects like Art and Design and Music are not currently included in the national curriculum at secondary Key Stage 4 level (ages around [14][15][16] [51]. Students in schools where these subjects are not available at this level may have limited opportunities to participate in artistic activities during school lessons where supplies, materials and resources are usually provided or subsidised.…”
Section: Discussionmentioning
confidence: 99%
“…Students in schools where these subjects are not available at this level may have limited opportunities to participate in artistic activities during school lessons where supplies, materials and resources are usually provided or subsidised. Further, more schools have also reduced or completely removed Music in the curriculum as early as for secondary year 7 students (around age 11) or have changed Music as an optional subject at secondary Key Stage 3 level (ages around [11][12][13][14] despite Music being in the National Curriculum for these school years [52,53]. In the absence of obligatory engagement in the arts, there has been an ongoing decrease in voluntary uptake of arts subjects at school [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier onset of musical training (i.e., aged ≤7 years) not only yielded greater cognitive and motor abilities ( Watanabe et al, 2007 ; Bailey and Penhune, 2013 ) but also boosted the development of empathy. For example, Kawase et al (2018) conducted a survey of 276 children aged 4–5 years and 6–7 years who started musical training at 1, 2, 4, and 6 years old. The results showed that the empathy scores of children aged 6–7 years who began training at 1 year old were greater than those who started at 4 years old, suggesting that early onset of music training positively influenced children’s empathy.…”
Section: Musical Training Boosts Empathy and Prosocial Behaviorsmentioning
confidence: 99%
“…Music activities also promote synchrony. Synchronization among group members is suggested to be a key to promoting sociability ( Weinstein et al, 2016 ; Kawase et al, 2018 ). Both social interaction and synchrony contribute to cultural identity and encourage the formation of cooperative networks.…”
Section: Psychological Mechanisms Of the Effect Of Musical Training In The Development Of Empathymentioning
confidence: 99%